P-039 Redefining 'success': a systematic review and meta-analysis comparing outcomes between incomplete and complete revascularization. (22nd July 2018) - Rizvi, A; Seyedsaadat, S; Murad, M; Brinjikji, W; Fitzgerald, S; Kadirvel, R; Rabinstein, A; Kallmes, D
Abstract : Background and purpose: Conventionally, 'successful' endovascular thrombectomy (EVT) had been defined as achieving revascularization of Thrombolysis In Cerebral Infarction (TICI)−2B or greater, rather than as 'complete' (TICI-3) versus 'incomplete' (TICI-2b) revascularization. We performed a systematic review and meta-analysis of studies comparing clinical outcomes between patients with TICI-2B and TICI-3 revascularization. Methods: Multiple databases were searched for relevant publications between January 2003 and November 2017. Studies comparing outcomes between TICI-2B and TICI-3 group of acute ischemic stroke (AIS) patients treated with EVT were included. Random effects meta-analysis was performed to evaluate outcomes among TICI-2B and TICI-3 groups. The following outcomes were assessed: good neurologic outcome (modified Rankin Scale [mRS] ≤2 at day 90), mortality, and intracerebral hemorrhage (ICH). The I 2 statistic was used to express the proportion of heterogeneity that is not attributable to chance. Results: Twenty three studies comprising 2577 patients were identified (figure 1). Patients with TICI-2B revascularization had mRS ≤2 at day 90 rates of 46% (373/807) compared with 67% (478/710) for TICI-3 patients (odds ratio [OR] 0.44, 95% confidence interval [CI] 0.35 to 0.56). Mortality rates were significantly higher in TICI-2B group (62/498, 13%) than in TICI-3 group (42/585, 7%) (OR 1.95, 95% CI 1.27 to 2.99). The ICH rates were also significantly higher in TICI-2B group as compared to TICI-3 group (23% [85/369] vs 14% [51/369]; OR 2.40, 95% CI 1.49 to 3.86) (table 1). Conclusions: Differences in all major outcome measures were markedly better in patients with complete versus incomplete but still 'successful' revascularization using prior thresholds, with odds ratios on the order of those seen in recent definitive trials comparing EVT to intravenous tissue plasminogen activator. The research community should consider redefinition of successful revascularization to reflect these patient-centric findings. Disclosures: A. Rizvi: None. S. Seyedsaadat: None. M. Murad: None. W. Brinjikji: None. S. Fitzgerald: None. R. Kadirvel: None. A. Rabinstein: None. D. Kallmes: None.